"Oh and how things just don't change, the more things stay the same": Reflections on SenseCam images 18 months after capture - Lindley, Siân; Glancy, Maxine; Harper, Richard; Randall, Dave; Smyth, Nicola (International Journal of Human-Computer Studies, 2011)
This paper presents an exploration of how images captured by a wearable camera, SenseCam, might foster reflection on everyday experiences. SenseCams were provided to multiple members of four households who wore them simultaneously and reviewed the images after one week, and then again after a period of 18 months. The findings reveal how images captured by different family members led to new insights around normally unremarkable routines, and provided new perspectives on how children experienced the world, while the 18 month interval prompted some reinterpretation of the past and made participants aware of incremental changes in their everyday lives. Implications for the design of tools to support reflection on personal experience are suggested and remarks about the concept of memory collection devices made.